IDENTIFIKASI PENERIMAAN BEASISWA DIPA MENGGUNAKAN METODE BACKWARD CHAINING - Wahyu Iskandar (Jupiter: Journal of Computer & Information Technology, 2020)
Scholarships are generally a provision of fees for education for students who arestill actively attending lectures at a tertiary institution. The scholarship so thatit can help students to finance their needs during college. The backwardchaining method can facilitate the campus bureaucrats in determining studentswho are entitled to receive scholarships. Backward Chaining is a model inreverse of hypotheses, a potential or conclusion that must be proven by facts thatsupport the hypothesis. The backward chaining model in receiving scholarshipstakes some data from existing variable criteria such as active lecture certificates,student cumulative achievement indexes, attaching TOEFL certificate, identitycard, and curriculum vitae. Next, make a decision tree from the data variables thatexist, and finally is implemented. The results of this study have an accuracy of 95%,which can be recommended to get the scholarship and this method can facilitatethe determination of scholarship acceptance. The backward chaining method isvery effective and accurate in determining DIPA scholarship recipients with anaccuracy rate of 95%, making it easier for the North Sumatra state Islamicuniversity community to select students who are eligible to receive.